Dose-Dependent Von Willebrand Factor Inhibition by Aptamer BB-031 Correlates with Thrombolysis in a Microfluidic Model of Arterial Occlusion - Susan M. Shea; Kimberly A. Thomas; Rassam M. G. Rassam; Emily P. Mihalko; Christina Daniel; Bruce A. Sullenger; Philip C. Spinella; Shahid M. Nimjee (MDPI AG, 2022)
Von Willebrand Factor (VWF) plays a critical role in thrombus formation, stabilization, and propagation. Previous studies have demonstrated that targeted inhibition of VWF induces thrombolysis when administered in vivo in animal models of ischemic stroke. The study objective was to quantify dose-dependent inhibition of VWF-platelet function and its relationship with thrombolysis using BB-031, an aptamer that binds VWF and inhibits its function. VWF:Ac, VWF:RCo, T-TAS, and ristocetin-induced impedance aggregometry were used to assess BB-031-mediated inhibition of VWF. Reductions in original thrombus surface area and new deposition during administration of treatment were measured in a microfluidic model of arterial thrombolysis. Rotational thromboelastometry was used to assess changes in hemostasis. BB-031 induced maximal inhibition at the highest dose (3384 nM) in VWF:Ac, and demonstrated dose-dependent responses in all other assays. BB-031, but not vehicle, induced recanalization in the microfluidic model. Maximal lytic efficacy in the microfluidic model was seen at 1692 nM and not 3384 nM BB-031 when assessed by surface area. Minor changes in ROTEM parameters were seen at 3384 nM BB-031. Targeted VWF inhibition by BB-031 results in clinically measurable impairment of VWF function, and specifically VWF-GPIb function as measured by VWF:Ac. BB-031 also induced thrombolysis as measured in a microfluidic model of occlusion and reperfusion. Moderate correlation between inhibition and lysis was observed. Additional studies are required to further examine off-target effects of BB-031 at high doses, however, these are expected to be above the range of clinical targeted dosing.